Conjunctival histopathological changes and clinical tear film in children with atopic dermatitis - Bayat, Alper Halil; Aksoy Aydemir, Gözde; Aydemir, Emre; Özkan, Hacı Hasan; Yardımcı, Gürkan; Aydın Türk, Bilge; Özkul Kılınç, Emine (My University, 2024)
Purpose: Evaluation of changes in the ocular surfaces in children with a diagnosis of atopic dermatitis (AD). Methods: Thirty-six children with a diagnosis of AD (Eye-AD group) and 40 healthy subjects (Eye-HS group) were enrolled in this prospective case-control study. Tear film break-up time (T-BUT), Schirmer tear test (STT), conjunctival impression cytology (CIC), tear meniscus height (TMH), tear meniscus area (TMA), and ocular surface disease index (OSDI) were measured. Results: The participants were similar in terms of demographic characteristics, such as mean age and gender (p > 0.05). The mean T-BUT was 9.3 ± 2.22 s (5 - 16) in the Eye-AD group and 11.83 ± 2.03 s (7 - 16) in the Eye-HS group. The mean STT was 11.12 ± 3.28 mm (5 - 21) in the Eye-AD group and 15.44 ± 3.8 mm (8 - 20) in the Eye-HS group (p < 0.001, p < 0.001, respectively). The mean OSDI scores were 13.12 ± 1.41 (10 - 15) in the Eye-AD group and 13.97 ± 2.93 (8 - 20) in the Eye-HS group (p = 0.052). Mean TMH and TMA were 306.48 ± 7.29 µm and 0.22 ± 0.004 mm2, respectively, in the Eye-AD group, and 312.94 ± 5.31 µm and 0.027 ± 0.005 mm2, respectively, in the Eye-HS group. In the CIC analyses, 22 of the samples in the Eye-AD group and 35 in the Eye-HS group had a classification of grade 0, 10 in the Eye-AD group and 5 in the Eye-HS group had a classification of grade 1, and 4 in the Eye-AD group and none in the Eye-HS group had a classification of grade 2 (p = 0.015). Conclusion: Pediatric patients with AD may have significant changes in conjunctival histopathology. These changes can be manifested in the tests used to measure the tear film. Dry eye was shown to be present in the majority of children with AD.

Zweck: Die Beurteilung von Veränderungen der Augenoberfläche bei Kindern mit der Diagnose atopische Dermatitis (AD). Methoden: In dieser prospektiven Fall-Kontroll-Studie wurden die Augen von 36 Kindern mit der Diagnose AD (Augen-AD-Gruppe) und 40 gesunden Probanden (Augen-HS-Gruppe) aufgenommen. Die Werte für die Aufreißzeit des Tränenfilms (T-BUT), den Schirmer-Tränentest (STT), die konjunktivale Impressionszytologie (CIC), die Tränenmeniskushöhe (TMH), die Tränenmeniskusfläche (TMA) und den Augenoberflächenkrankheitsindex (OSDI) wurden ermittelt und gesammelt. Ergebnisse: Die Teilnehmer waren hinsichtlich demografischer Merkmale wie Durchschnittsalter und Geschlecht ähnlich (p > 0,05). Die mittlere T-BUT betrug 9,3 ± 2,22 s (5 – 16) in der Eye-AD-Gruppe, 11,83 ± 2,03 s (7 – 16) in der Eye-HS-Gruppe, STT 11,12 ± 3,28 mm (5 – 21) in der Eye-AD-Gruppe und 15,44 ± 3,8 mm (8 – 20) in der Eye-HS-Gruppe (p < 0,001 bzw. p < 0,001). Die mittleren OSDI-Werte betrugen 13,12 ± 1,41 (10 – 15) in der Eye-AD-Gruppe und 13,97 ± 2,93 (8 – 20) in der Eye-HS-Gruppe (p = 0,052). Die mittleren TMH- und TMA-Werte betrugen 306,48 ± 7,29 µm und 0,22 ± 0,004 mm2 in der Eye-AD-Gruppe und 312,94 ± 5,31 µm und 0,027 ± 0,005 mm2 in der Eye-HS-Gruppe. In den CIC-Analysen hatten von den Proben 22 in der Eye-AD-Gruppe und 35 in der Eye-HS-Gruppe eine Klassifizierung mit Grad 0, 10 in der Eye-AD-Gruppe und 5 in der Eye-HS-Gruppe eine Klassifizierung mit der Grad 1 und 4 in der Eye-AD-Gruppe und keiner in der Eye-HS-Gruppe hatte eine Klassifizierung von Grad 2 (p = 0,015). Schlussfolgerung: Pädiatrische Patienten mit AD können erhebliche histopathologische Veränderungen der Bindehaut aufweisen. Diese Veränderungen können sich in den Tests zur Messung des Tränenfilms manifestieren. Es wurde gezeigt, dass bei der Mehrzahl der Kinder mit AD ein trockenes Auge vorliegt.
Histopathologische veränderungen der bindehaut und klinischer tränenfilm bei kindern mit atopischer dermatitis
Keywords: Cornea; Paediatric Ophthalmology; Atopic Dermatitis; Dry Eye; Kinderophthalmologie; Kornea; Atopische Dermatitis; Trockenes Auge